BLANCHE DAN STANLEY, DUA ALTER-EGO TENNESSEE WILLIAMS DALAM A STREETCAR NAMED DESIRE: *) SEBUAH TINJAUAN PSIKOANALISIS - Iswalono, Sugi; Nurhayati, Ari; Anggraeni, Niken (Diksi, 2015)
This article is about a research aimed at finding the forms of Williams' desire which is unfulfilled or repressed into his unconscious mind as sublimated in his play, A Streetcar Named Desire. In other words, Williams' main invented characters, Blanche and Stanley, whose personalities are shaky or chaotic, represent the expression of the playwright's unbalanced personality which is sublimated in the play. The research is conducted by tracing Williams' life and understanding the play A Streetcar Named Desire as well as the criticism on it and his other works of which the aspects are comparable. To come to the desired aim, psychoanalytic criticism is aptly opted to expose the issue. In relation to the various schools of psychoanalysis, the research applies Freud's psychoanalytic perspective, focusing on the relationship between the author and his work. The research results show the following. Firstly, A Streetcar Named Desire was written on the basis of Williams' life, especially his childhood and youth, in which he experienced unhappy and inharmonious relationship with his father and, as a consequence, it made his personality chaotic or unbalanced, which then brought about sexual perversion in him, making him a passive homosexual. Secondly, the perverted sexual behavior of his was as a matter of fact the manifestation of his rebellion against his father, which he then expressed through his work. Thirdly, such behavior was inappropriate in the American cultural and social life during his life span and, therefore, he had to repress his desire because it was impossible for him to release his libidinous drive so that, to avoid neurosis, he sublimated it in literature. In other words, A Streetcar Named Desire is the sublimation of Williams' repressed libido to express his rebellion against his father and to release his libidinous drive. In that case, he creates Stanley and Blanche as his fantasy to escape from his repression though only a minute's escape. Key words: Tennessee Williams, childhood, chaotic personality, libido, father, repression, neurosis, sublimation, Blanche, Stanley